(untitled) (Bangladesh Journal of Medical Science, 2009)
Objective: This study was undertaken to evaluate the antibody response of hepatitis B virus infection in patients on maintenance hemodialysis (MHD) by detecting different viral markers. Method: Study subjects comprised a total of 88 chronic kidney disease (CKD) patients from Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) and Bangabandhu Sheikh Mujib Medical University (BSMMU). Of them 63 patients on MHD and 25 predialysis patients served as cases and controls respectively. Clinical history was taken and serological markers for HBV (HBsAg, Anti-HBs, and Anti-HBc) were determined by using ELISA. Results: Hepatitis B virus was positive in 1.6% of maintenance hemodialysis (MHD) patients and in 16% of controls (p<0.02). Anti-HBc antibody was positive in 62% of dialysis patients and 72% of controls (p=NS) and the positivity was significantly associated in dialysis subjects with longer duration of dialysis (18 ± 22 vs. 10 ± 7, months, p<0.04), multiple units of blood transfusions (22 ± 29 vs. 10 ± 12, units, p<0.04) and more reuse of dialyzer (3 ± 1 vs. 2 ± 1, times, p<0.03) than the negative ones. Among MHD patients 84% were vaccinated against HBV with a schedule of 3 (79%) and 4 (21%) doses and protective antibody titer (>10 IU/L) was found in 57%. None of the controls were vaccinated but 66% had protective titer indicating post exposure natural immunity. Conclusions: Hepatitis B virus positivity was significantly higher among the predialysis subjects compared to dialysis group. Key words: Hepatitis B virus, Antibody response, Hemodialysis doi: 10.3329/bjms.v8i1.3185 Bangladesh Journal of Medical Science Vol.8 No. 1-2; 2009 15-21